Dataset and R Code for: Mental health impacts in Argentinean college students during COVID-19 quarantine - López Steinmetz, Lorena Cecilia (2021)
Fil: López Steinmetz, Lorena Cecilia. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.